‘The more we verify it, the more truth there is’: Producing the truth and expertise in public policy - Karel Čada; Petra A. Honová (International Review of Public Policy)
Between 2005 and 2006, the Czech government imposed a forced administration on the General Health Insurance Fund (VZP) because of economic problems. This unprecedented step in Czech public policy resulted in a debate. The VZP is the largest insurance fund in the Czech Republic, and this case has been one of the most severe institutional crises in Czech health policy. Employing analysis of 38 television-hosted debates, we emphasise how the actors negotiated accountability, credibility and truth. This paper aims to identify the discursive and rhetorical resources used by the involved parties to manage what was at stake in the debate: to maintain their credibility and legitimacy and to manage factuality. We follow Collins and Evans’s (2002) approach to expertise and distinguish four types of expertise: contributory, interaction, institutionally recognised, and experience-based. These different kinds of expertise use other vehicles of corroboration and factual evaluation. We opt for a more nuanced approach to how involved actors argue and what rhetorical strategies are relevant in different contexts.